Assessment of the Seismic Behavior of a Precast Reinforced Concrete Industrial Building with the Presence of Horizontal Cladding Panels - Ostetto, Liana (2021)
The latest earthquakes in Europe exposed some critical problems in the connections of cladding panels in industrial precast reinforced concrete (PRC) structures. These connections did not perform as desired, causing the panels to fall, leading to significant nonstructural damage that resulted in the loss of human life and significant socio-economic impacts due to the interruption of business. Furthermore, in addition to the behavior of the cladding system itself, it is still not clear to what extent it can influence the overall seismic performance of the main structure. Making use of a simplified macroelement, the present study assesses the seismic performance of commonly employed cladding-to-structure connections, as well as the interaction of cladding panels with industrial PRC buildings. The analyses were carried out considering a PRC building representative of a Portuguese industrial park, studied with and without cladding panels. The seismic behavior of the structure was assessed considering both nonlinear static and dynamic procedures.